2017
DOI: 10.1136/ejhpharm-2017-001242
|View full text |Cite
|
Sign up to set email alerts
|

Identification and prioritisation of risks in a hospital pharmacy using healthcare failure mode and effect analysis

Abstract: ObjectivesThe goals of this project included identifying the processes and subprocesses performed in hospital pharmacies, identifying potential adverse events, detecting failure modes and the causes of errors, prioritising the risks identified and designing a map of risks for hospital pharmacies.MethodsA task force composed of hospital pharmacy staff was committed to update the diagram of processes and design a map of processes performed in hospital pharmacies. Risks were identified by failure mode and effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Several studies have recognized the importance that HFMEA has when it comes to identifying failure modes (FMs), its causes and consequences in a variety of health-care processes, such as distribution and the administration of medicines, parenteral nutrition, and chemotherapy (31)(32)(33)(34)(35)(36)(37)(38)(39). As recently demonstrated in a study by Castro Vida et al (40), the HFMEA has been conducted in all processes and sub-processes in hospital pharmacies except for medicine-shortage management (40).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have recognized the importance that HFMEA has when it comes to identifying failure modes (FMs), its causes and consequences in a variety of health-care processes, such as distribution and the administration of medicines, parenteral nutrition, and chemotherapy (31)(32)(33)(34)(35)(36)(37)(38)(39). As recently demonstrated in a study by Castro Vida et al (40), the HFMEA has been conducted in all processes and sub-processes in hospital pharmacies except for medicine-shortage management (40).…”
Section: Introductionmentioning
confidence: 99%
“…For risk assessment and decision making, it is necessary to have complete information on the internal and external environment and risk carriers [9]. In accordance with this, we conducted a content analysis [6,8,[10][11][12][13][14], which allowed us to identify the main sources of risk, to identify them, and to classify them by the degree of consequences ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…To reduce the criticality, corrective actions have been proposed—mainly, the instauration of the double-checking before delivery. In the study of Castro Vida et al , 99 failures were identified, including 50 failures associated with medicine management and inpatient pharmaceutical care processes, with 11 failures considered as critical 29. The large number of failure modes identified in their study can be explained by more diversified pharmaceutical activities in comparison with our activity: pharmacotechnics and drug compounding, pharmacokinetics, nutrition and research.…”
Section: Discussionmentioning
confidence: 99%